Design and Development of an Android-Based Interactive Learning Media for Grade VIII Statistics using the ADDIE Model - Rahayu, Lestari; Prakisya, Nurcahya Pradana Taufik; Hatta, Puspanda; Wafa, Alfian Fawaidil; Herianto, Tulus Joseph (Jurnal Media Informasi Teknologi, 2025)
In the 21st-century learning era, students in several regions of Indonesia still use conventional media such as whiteboards and textbooks in mathematics education. This leads to student boredom and relatively low learning outcomes because they are more interested in playing with smartphones rather than studying. The solution to this problem is to utilize Information and Communication Technology (ICT) as a learning medium. The purpose of this research is to develop, evaluate the feasibility, and determine user perceptions of an interactive Android-based learning media for Grade VIII statistics in junior high school. This research follows a research and development design consisting of three stages: development using the ADDIE method, feasibility analysis, and user perception analysis. The result of the development stage is a valid interactive Android-based learning media. The feasibility analysis results indicate that the media is highly feasible with a rating of 92.5% from media experts and 95% from subject matter experts. The user perception analysis shows that 84.4% of students strongly agree with the usefulness aspect of this media, and 89.5% of students strongly agree with the ease of use aspect. Therefore, it can be concluded that this interactive learning media is worthy, user-friendly, and beneficial in the learning process.